Effect of Irrigation Levels and Frequencies on Yield, Quality and Water Use Efficiency of Capsicum Grown under Protected Conditions - Kumar, Ramesh; Kumari, Prabal; Kumar, Sandeep (International Journal of Bio-resource and Stress Management, 2016)
The present investigation was carried out at Experimental Research Farm of the Department of Vegetable Science, Dr. Y.S. Parmar University of Horticulture and Forestry, Nauni, Solan (HP), India during spring-summer seasons of year 2010 and 2011 to standardize the irrigation scheduling for improving capsicum yield, quality and water use efficiency under protected conditions. The experiment was laid down in RCBD with seven treatments having three irrigation depths, two intervals and a farmers practice. The data were recorded on fruit length (cm), fruit breadth (cm), average fruit weight (g), number of fruits plant-1, total biomass production (g/plant), yield plot-1 (kg), total soluble solids (°B), ascorbic acid (mg 100 g-1), root rot incidence (%), water productivity (kg m-2 cm-1) and soil moisture (%). The perusal of the pooled data revealed that different levels and frequencies of irrigation produced significant differences with regards to different traits under study. The treatment with 0.50 cm of irrigation at alternate day resulted in maximum fruit breadth (6.53 cm), average fruit weight (95.20 g), number of fruits plant-1 (18.26), total biomass production (165.38 g plant-1) and highest economic yield plot (36.17 kg plot-1) and along with moderate water productivity (0.25 kg m-2 cm-1), may be recommended for commercial cultivation of capsicum in the hilly regions under naturally ventilated polyhouses. However, the treatment with 0.25 cm of irrigation at alternate day recorded maximum water productivity (0.43 kg m-2 cm-1) and total soluble solids (5.30%) with moderate yield (30.58 kg plot-1) and lowest root rot incidence (2.76%), may be suggested for the high water scare areas for the successful cultivation of capsicum under protected conditions.